EFFECT OF HOTEL AND RESTAURANT TAX REVENUES ON LOCAL NATIVE INCOME IN SEMARANG CITY - Ajun Nurul Afa; Hendri Hermawan A, M.S.I (Annals of the University of Craiova for Journalism, Communication and Management)
This study aims to analyze the influence of hotel and restaurant tax revenues in Semarang City. The research uses descriptive quantitative methods with a secondary data analysis approach. The object of this research is the large contribution of hotel and restaurant taxes to the original income of the Semarang City area which includes reports on the realization of local native income, the level of effectiveness of realization, the realization of hotel and restaurant taxes. The authors used secondary data obtained from various official local government sources. Hotel and restaurant tax contributions are still very less contributing because the value is below 10%. The realization of regional income is very effective because the average percentage exceeds 100%. The author lists hotel tax revenue data from 2017-2021, and restaurant taxes from 2017-2021, the pandemic has also greatly affected hotel and restaurant tax revenues and there are obstacles in collecting information data, namely the lack of data updates on the official website of the Semarang City regional government. Suggestions for local governments to further develop and compile regional data periodically and systematically so that further research can be more actual and accurate.